Active whey protein edible films and coatings incorporating Lactobacillus buchneri for Penicillium nordicum control in cheese - Guimarães, Ana (2022)
Fungal contamination of food is responsible for health issues and food waste. In this work, the incorporation of a lactic acid bacteria (LAB) with antifungal properties (Lactobacillus buchneri UTAD104) into whey protein-based films and coatings was tested for the control of an ochratoxigenic fungi (Penicillium nordicum) in a cheese matrix. The incorporation of L. buchneri cells resulted in thicker films with less luminosity than control films and colour alteration. Nevertheless, cells inclusion did not alter moisture content, water vapour permeability, mechanical properties, hydrophobicity and chemical structure of the films. Whey protein films were able to maintain the viability of L. buchneri UTAD104 cells in 105 CFU/mL after 30 days of storage at 25 °C. When applied in cheese, films and coatings containing L. buchneri cells prevented fungal contamination for at least 30 days, while control cheeses with films and coatings either without LAB or with Lactobacillus casei UM3 (a strain without antifungal ability) showed fungal contamination during that period. Ochratoxin A was not found in cheeses treated with films and coatings containing L. buchneri UTAD104. Results showed that the inclusion of a LAB with antifungal properties in edible films and coatings can help to reduce or eliminate P. nordicum contamination in cheeses.